AB0216 Overexpression of Synovial Lining Peroxisome Proliferator-Activated Receptor-Gamma Coactivator-1β Involved in Joint Destruction through Upregulating MMP-3 in Rheumatoid Arthritis. (15th July 2016) - Jing, J.; Ma, J.-D.; Mo, Y.-Q.; Chen, L.-F.; Dai, L.
Abstract : Background: Our previous study showed that suppression of peroxisome proliferator-activated receptor-gamma coactivator-1β (PGC-1β) alleviated the secretion of matrix metalloproteinase (MMP)-3 from fibroblast-like synoviocytes and inhibited osteoclastogenesis in vitro. However, little was known about PGC-1β with joint destruction in RA patients. Objectives: To investigate the expression and correlation of synovial PGC-1β with joint destruction in RA patients. Methods: Eighty-one patients with active RA were recruited and followed up for one year. Serum MMP3 was detected by ELISA. Synovial tissue was obtained by closed-needle biopsy for H&E and immunohistochemistry staining for PGC-1β, MMP-3, CD3, CD20, CD38, CD68 and CD15. X-ray assessment of hand/wrist was repeated at baseline and one year and radiographic progression was defined as TSS≥0.5 unit. Results: (1) PGC-1β expression in RA was observed with intense nuclear staining in lining cells and sublining inflammatory cells (including macrophages, lymphocytes and plasma cells) which were significantly higher than osteoarthritis (OA) or orthopedic arthropathies (Orth.A, Fig. 1 A). (2) The percentage of lining PGC-1β+ cells significantly correlated with serum and synovial MMP-3 ( r =0.394 and 0.376, both P <0.01), as well as CRP, ESR, CD15+ neutrophils and CD68+ macrophages in sublining area of RA synovium ( r =0.266–0.356, all P <0.05), and the percentage of sublining PGC-1β+ cells significantly correlated with CRP, ESR, total synovitis score, CD3+ T cells, CD20+ B cells and CD38+ plasma cells, CD68+ macrophages in sublining area of RA synovium ( r =0.225-0.428, all P <0.05). (3) Forty-three (53%) RA patients had erosive disease (2013 EULAR definition) at baseline and their percentage of lining and sublining PGC-1β+ cells was significantly higher than non-erosive patients (both P <0.05, Fig. 1 B). Both percentages of lining and sublining PGC-1β+ cells were significantly correlated with mTSS, joint space narrowing and erosion subscore ( r =0.228-0.261, all P <0.05). (4) Thirty-nine patients had finished one year follow-up and 23% of them had radiographic progression. The percentage of lining PGC-1β+ cells was significantly higher in progressive patients than non-progressive patients [83% (79%–91%) vs 75% (65%–82%), P =0.002]. ROC curve analysis showed that the tradeoff value of lining PGC-1β+ cells for predicting 1-year radiographic progression was 78% with sensitivity 89% and specificity 70% (AUC=0.833, 95% CI: 0.689–0.978, P =0.003). (5) Serum and synovial MMP-3 were significantly higher in patients with high synovial lining PGC-1β than that in patients with low synovial lining PGC-1β (both P <0.05, Fig. 1 C–E). Multivariate logistic regression analysis showed that high lining PGC-1β+ cells was a significant predictor of 1-year radiographic progression after adjustment for synovial and serum MMP-3 (OR: 15.002, 95% CI: 1.43–156.698, P =0.024, Fig. 1 C). Conclusions: Overexpression of synovial lining PGC-1β might play important roles in aggravating joint destruction through upregulating MMP-3 in RA. Acknowledgement: This work was supported by National Natural Science Foundation of China (81471597), Specialized Research Fund for the Doctoral Program of Higher Education (20130171110075) and Guangdong Natural Science Foundation (2014A030313074). Disclosure of Interest: None declared